Líquidos iônicos: aplicação na síntese de β-dimetilaminovinil cetonas e na N-alquilação de pirazóis - Frizzo, Clarissa Piccinin (2007)
The synthesis of two 1-methyl-3-alkylimidazolium tetrafluoroborate (where alkyl = butyl, octyl; [BMIM]BF4 and [OMIM]BF4) based on room temperature ionic liquids (RTIL) is reported. The usefulness of these ionic liquids in organic synyhesis was evaluated through three reactions such as: (i) preparation of the N,N-dimethylenaminones (RCOCH=CHNMe2, where R = Ph, 4-Me-Ph, 4-F-Ph, 4-Cl-Ph, 4-Br-Ph, 4-O2N-Ph, fur-2-yl, tien-2-yl, pyrrol-2-yl, pyrid-2-yl, CH(OMe)2, octyl) from the condensation reaction of N,Ndimethylformamide dimethyl acetal with methylketones; (ii) preparation of the 6-dimethylamino-1,1,1-trifluoro-4-methoxy-3,5-dien-2-one [CF3COCH=CH(OMe)CH=CHNMe2, from the condensation reaction of N,Ndimethylformamide dimethyl acetal with appropriated 1,1,1-trifluoro-4-methoxy-3-penten-2- one and (iii) N-alkylation reaction of 3,5-dimethyl- and 5-trifluoromethyl-3-methyl-1Hpyrazoles, from the reaction of the N-H pyrazoles with alkyl halides (R1 X, where R1 = Bu, octyl, allyl, benzyl, CH₂CH₂CONEt₂). The reaction time, and the yields were investigated and this method showed advantages over the methods described in the literature.